PENENTUAN STRATEGI BAURAN PEMASARAN PELUMAS FOOD GRADE GREASE BERBAHAN DASAR KELAPA SAWIT DI KABUPATEN PURBALINGGA - Tri Yanto; Aiman Abulkhair (Universitas Sebelas Maret, 2016)
The objective of this study is to determine the merchant and the user preferences to the specification lubricating grease lubricants, color lubricants, package sizes, shape packaging labels, distribution of lubricants, promotion, and price. Sampling using purposive sampling technique. Analysis of data using friedman test with 5% error level. If there are differences then test ed further by LSD. The results of this research note that lubricant specifications preferred by merchants, which is preferred by the user while the grease is food grade lubricants and general machinery lubrication; the color lubricant preferred by merchantsis natural and blue, which is preferred by the user while the grease is the natural color; pack sizespreferred by merchants is size 350 g and 150 g with packing cup and bulk, while users liked the size of 350 g with packing cup; form label lubricants are preferred by merchants grease a round shape that is labeled with red and green as well as a square shape label in red, while the grease is preferred by the user labels round and square shapes in red; lubricants distribution are preferred by merchants grease ie grocery stores, retail stores, repair shops, and peddlers, while the grease is preferred by the user distribution through grocery stores and workshops; lubricants promotion are preferred by merchants grease is through internet media, banners, brochures, radio and posters, while users of grease liked by media promotion banners, brochures and posters; the price lubricant grease favored by merchants as preferred by the user of grease that low price low quality, medium quality and medium price high price of high quality.